PENGARUH LATIHAN SINGLE LEG PUSH OFF TERHADAP POWER OTOT TUNGKAI PADA PERMAINAN BULU TANGKIS SISWA TIM O2SN SMP NEGERI 22 PEKANBARU - Ramos Ramos; Slamet Slamet; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : From the result of field research during practice, researcher finds the problem that there is a lack of leg muscles power on Badminton team O2SN of the students SMPN 22 Pekanbaru. Based on the program, the researcher gives the training of single leg push off, that can increase the power of leg muscles and gives the training program intensively. The type of this research is experimental research with the research purpose is to see the influence of training. The population of the research is 6 people Badminton team O2SN of the students SMPN 22 Pekanbaru. The sampling technique is total sampling, which the total of population is used as sample. The data collected from pree-test and post-test. The instrument of this research is single leg push off as a tool to measure the leg muscles power. The analysis is conducted by using t-test. Based on data analysis and the discussion, it can’t be concluded that there is a single lef push offexercise effect to the leg muscles power on the Badminton team O2SN of the students SMPN 22 Pekanbaru that was proven by Tresult while 1,265 dan Ttable 2,015. It meansi Tresult ˂ Ttable on level of ɑ=0,05.Keyword: Single Leg Push Off Exercise, Leg Muscles, Power on Badminton